Acessibilidade e preservação no patrimônio cultural da cidade de Ouro Preto, Minas Gerais - Raissa Keller e Costa (2016)
The historic cities, monuments and protected sites as cultural heritage are important in the establishment of society and its identity. Therefore, there is a need to preservation so that future generations may enjoy this expression of local culture. However, accessibility is a key factor for this social function to be possible. It allows everyone to have reach places and to experience the heritage environment with autonomy and safety. Despite being a civil right in Brazil, accessibility is not always achieved due to the challenges of creating heritage interventions in important historic sites such as the city of Ouro Preto, Minas Gerais. This study seeks to understand and discuss the accessibility conditions in both Tiradentes Square and the Town Council Hall of Ouro Preto. The research methodology adopted in this study is based on qualitative research and documental research at interdisciplinary range. As result, evidency factors supporte inaccessibility conditions in the Town Hall of Ouro Preto. Although several environmental adaptations have been made throughout its history, none of them have met past and current law requirements on accessibility.